2009
DOI: 10.1099/ijs.0.65718-0
|View full text |Cite
|
Sign up to set email alerts
|

Serratia nematodiphila sp. nov., associated symbiotically with the entomopathogenic nematode Heterorhabditidoides chongmingensis (Rhabditida: Rhabditidae)

Abstract: The genus Serratia belongs to the family Enterobacteriaceae of the class Gammaproteobacteria. Some members of the genus Serratia have clinical importance (Grimont & Grimont, 1992;Brenner, 1984) and other members produce pigments identified as prodigiosin (Hearn et al., 1970;Gerber, 1975). A subspecies of Serratia marcescens (S. marcescens subsp. sakuensis) and a urea-dissolving species (Serratia ureilytica) have been described previously by Ajithkumar et al. (2003) and Bhadra et al. (2005), respectively. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…24, 2011 SERRATIA INFECTIONS 761 and DNase production, and it has a lower mol% GϩC (49 to 52% for S. fonticola, compared to 52 to 60% for other members of the genus Serratia) (159) (36). In 2009, a red-pigmented organism was isolated from the intestine of Heterorhabditidoides chongmingensis, an entomopathogenic nematode (425). This isolate, named S. nematodiphila, was also fluorescent (425).…”
Section: Taxonomy Of Other Serratia Speciesmentioning
confidence: 99%
“…24, 2011 SERRATIA INFECTIONS 761 and DNase production, and it has a lower mol% GϩC (49 to 52% for S. fonticola, compared to 52 to 60% for other members of the genus Serratia) (159) (36). In 2009, a red-pigmented organism was isolated from the intestine of Heterorhabditidoides chongmingensis, an entomopathogenic nematode (425). This isolate, named S. nematodiphila, was also fluorescent (425).…”
Section: Taxonomy Of Other Serratia Speciesmentioning
confidence: 99%
“…The antibiotic susceptibility of the isolates WPRA3, SM11-3J and SC-G18 were similar to other non-pathogenic Serratia species such as S. marcescens subsp. sakuensis JCM 11315 [10], but they were more resistant to antibiotics than S. nemathodiphila DZ0503SBS1 [11], although in comparison with pathogenic Serratia species such as S. marcescens strain 08 [12] and S. marcescens [13] they were more susceptible to antibiotics. Table 1 shows the antibiotic susceptibility of isolates WPRA3, SM11-3J and SC-G18 in comparison with other Serratia species.…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%
“…Isolates WPRA3, SM11-3j and SC-G18 were unable to grow in metal-agar media at any concentration = S. marcescens subsp. sakuensis JCM 11315T [11]; F 6 = S marcescens strain 08 [13]; G 7 = S. marcescens [14]; R = resistance; S = susceptible; NA = not available. CdSO 4 --- [7].…”
Section: Heavy Metal Resistancementioning
confidence: 99%
“…Recently, Galleria trap experiments and direct isolation methods have, however, revealed nematodes other than members of the Steinernematidae and Heterorhabditis (Young-Keun et al, 2007;Zhang et al, 2008). Moreover, Zhang and colleagues (Zhang et al, 2009) reported a new species of Serratia that they found symbiotically associated with a new entomopathogenic nematode genus discovered earlier (Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%